2004
DOI: 10.1002/chin.200503081
|View full text |Cite
|
Sign up to set email alerts
|

Curtius Rearrangement and Wolff Homologation of Functionalized Peroxides.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This method is widely employed in the transformation of carboxylic acids into carbamates and ureas. Acyl azides are usually prepared from carboxylic acid derivatives such as acyl chlorides, , mixed anhydrides, , and hydrazides. , Subsequent isocyanate intermediates can be trapped by a variety of nucleophiles to provide the carbamate derivatives. The acid chloride method is not suitable for acid-sensitive functionalities.…”
Section: Methods For the Synthesis Of Carbamatesmentioning
confidence: 99%
“…This method is widely employed in the transformation of carboxylic acids into carbamates and ureas. Acyl azides are usually prepared from carboxylic acid derivatives such as acyl chlorides, , mixed anhydrides, , and hydrazides. , Subsequent isocyanate intermediates can be trapped by a variety of nucleophiles to provide the carbamate derivatives. The acid chloride method is not suitable for acid-sensitive functionalities.…”
Section: Methods For the Synthesis Of Carbamatesmentioning
confidence: 99%
“…Dussault and Xu found that diazoketones containing peroxy substituents undergo Wolff rearrangement to afford homologated peroxyalkanoates to an extent that was reaction condition dependent (Scheme 46). 107 Thus, reaction of diazoketones 18 and 19 with silver benzoate and triethylamine in methanol furnished homologated peroxy products in excellent yield. These conditions were much less successful when applied to substrates 20 and 21.…”
Section: Wolff Rearrangementmentioning
confidence: 99%